Відповідь:
X = 2 1/3
Покрокове пояснення:
3 3/10 ÷ (1/4 × X + 5/12) - 2 3/5 = 7/10
3 3/10 ÷ (1/4 × X + 5/12) = 7/10 + 2 6/10
3 3/10 ÷ (1/4 × X + 5/12) = 3 3/10
1/4X + 5/12 = 3 3/10 ÷ 3 3/10
1/4X + 5/12 = 1
1/4X = 12/12 - 5/12
1/4X = 7/12
X = 7/12 : 1/4
Відповідь:
X = 2 1/3
Покрокове пояснення:
3 3/10 ÷ (1/4 × X + 5/12) - 2 3/5 = 7/10
3 3/10 ÷ (1/4 × X + 5/12) = 7/10 + 2 6/10
3 3/10 ÷ (1/4 × X + 5/12) = 3 3/10
1/4X + 5/12 = 3 3/10 ÷ 3 3/10
1/4X + 5/12 = 1
1/4X = 12/12 - 5/12
1/4X = 7/12
X = 7/12 : 1/4
X = 2 1/3